CBF oscillations induced by trigeminal nerve stimulation protect the pericontusional penumbra in traumatic brain injury complicated by hemorrhagic shock - Chunyan Li (Nature Portfolio, 2021)
Abstract Traumatic peri-contusional penumbra represents crucial targets for therapeutic interventions after traumatic brain injury (TBI). Current resuscitative approaches may not adequately alleviate impaired cerebral microcirculation and, hence, compromise oxygen delivery to peri-contusional areas. Low-frequency oscillations in cerebral blood flow (CBF) may improve cerebral oxygenation in the setting of oxygen deprivation. However, no method has been reported to induce controllable oscillations in CBF and it hasn’t been applied as a therapeutic strategy. Electrical stimulation of the trigeminal nerve (TNS) plays a pivotal role in modulating cerebrovascular tone and cerebral perfusion. We hypothesized that TNS can modulate CBF at the targeted frequency band via the trigemino-cerebrovascular network, and TNS-induced CBF oscillations would improve cerebral oxygenation in peri-contusional areas. In a rat model of TBI complicated by hemorrhagic shock, TNS-induced CBF oscillations conferred significant preservation of peri-contusional tissues leading to reduced lesion volume, attenuated hypoxic injury and neuroinflammation, increased eNOS expression, improved neurological recovery and better 10-day survival rate, despite not significantly increasing CBF as compared with those in immediate and delayed resuscitation animals. Our findings indicate that low-frequency CBF oscillations enhance cerebral oxygenation in peri-contusional areas, and play a more significant protective role than improvements in non-oscillatory cerebral perfusion or volume expansion alone.